Technological prospection of the biological activities of Plectranthus amboinicus (Loureiro) Sprengel: an integrative review (Research, Society and Development, 2021)
Plectranthus amboinicus (Loureiro) Sprengel is popularly known as malvariço or indian borage. This paper carries out the technological prospecting of this species with an emphasis on its biological activities. The research consisted of an integrative literature review based on information collected from patent and electronic databases. Initially, 3019 results were obtained, which, after the screening, selection and analysis process, resulted in 55 articles and 48 patent documents. It was found that 77.08% (n=37) of patent deposits refer to obtaining or improving the process and 22.92% (n=11) to the finished product related to the following indications: wound healing, mainly in diabetics, followed by treatment of rheumatoid arthritis, hepatocellular carcinomas, breast cancer and melanoma, treatment for acne caused by P. acnes, S. aureus and P. aeruginosa, oral cavity cleansing agent, treatment for osteoporosis, nutraceutical composition for lactation and insect repellent. In the databases of scientific articles, 55 documents were selected, proving the following actions: antimicrobial, antioxidant, anticarcinogenic, anti-inflammatory, diuretic, nephroprotective, larvicide, analgesic, veterinary food additive, anti-leishmania, antipsoriasis, antidiarrheal, antidiabetic, hepatoprotective and anthelmintic. The scientific studies analyzed reaffirm other actions reported in popular use, but which are not described in the patent processes. Therefore, there are many proven biological properties of P. amboinicus that should be further explored and exploited in the pharmaceutical, cosmetic and food sectors in order to generate new products and patents.